Freestyle stroke parameters of national level swimmers with physical impairments - Perez-Tejero, J.; Almena, A.; Coterón, J.; Navandar, A.; Veiga, S. (Revista Internacional de Ciencias del Deporte, 2018)
Swimmers with physical impairments during competition for freestyle swimming are grouped according to their functional classification in ten classes. Stroke length, stroke rate, stroke index and clean swimming speed have been studied previously at elite level, but not at national level. Therefore, the aim of this study was to assess the four mentioned variables and performance time regarding functional class and gender in a sample of national level swimmers with physical impairments at the 100 m freestyle. Fourteen female (classes S4, S5, S7; S8, S9 and S10) and 29 male (classes S4, S5, S6, S7 S8, and S10) swimmers were recorded during the Winter Spanish Championship for Adapted Swimming. Classical fixed distances method was used for race analysis. Based on the results, stroke length, stroke index, clean swimming speed (and not stroke rate) values increased and turn time decreased significantly (p < 0.01) according to the functional class for both males and females from S4 up to S10; with the exception of the S5 male class, with better results (not significant, ns) than S8 in stroke index, or than S7 for clean swimming speed. Significant differences in stroke rate, stroke length and time for males between first and second lap were found, while differences were registered in stroke rate, stroke index, clean swimming speed and time for females. The presented profiling allows to frame performance for long term development of swimmers with physical impairments and also coaches can use the results to determinate the best relationship between stroke rate and stroke length for their swimmers, advice development and talent identification.